A multi‐institutional randomized controlled trial comparing first‐generation transrectal high‐resolution micro‐ultrasound with conventional frequency transrectal ultrasound for prostate biopsy. Issue 2 (28th November 2020) - Pavlovich, C. P.; Hyndman, M. E.; Eure, G.; Ghai, S.; Caumartin, Y.; Herget, E.; Young, J. D.; Wiseman, D.; Caughlin, C.; Gray, R.; Wason, S.; Mettee, L.; et al.
Abstract: Objectives: To study high‐frequency 29 MHz transrectal side‐fire micro‐ultrasound (micro‐US) for the detection of clinically significant prostate cancer (csPCa) on prostate biopsy, and validate an image interpretation protocol for micro‐US imaging of the prostate. Materials and methods: A prospective randomized clinical trial was performed where 1676 men with indications for prostate biopsy and without known prostate cancer were randomized 1:1 to micro‐US vs conventional end‐fire ultrasound (conv‐US) transrectal‐guided prostate biopsy across five sites in North America. The trial was split into two phases, before and after training on a micro‐US image interpretation protocol that was developed during the trial using data from the pre‐training micro‐US arm. Investigators received a standardized training program mid‐trial, and the post‐training micro‐US data were used to examine the training effect. Results: Detection of csPCa (the primary outcome) was no better with the first‐generation micro‐US system than with conv‐US in the overall population (34.6% vs 36.6%, respectively, P = .21). Data from the first portion of the trial were, however, used to develop an image interpretation protocol termed PRI‐MUS in order to address the lack of understanding of the appearance of cancer under micro‐US. Micro‐US sensitivity in the post‐training group improved to 60.8% from 24.6% ( P < .01), while specificity decreased (from 84.2% to 63.2%). Detection of csPCa in the micro‐US arm increased by 7% after training (32% to 39%, P < .03), but training instituted mid‐trial did not affect the overall results of the comparison between arms. Conclusion: Micro‐US provided no clear benefit over conv‐US for the detection of csPCa at biopsy. However, it became evident during the trial that training and increasing experience with this novel technology improved the performance of this first‐generation system. Abstract : In this work high‐frequency 29 MHz transrectal side‐fire micro‐ultrasound (US) for the detection of clinically significant prostate cancer on prostate biopsy is studied, and an image interpretation protocol for micro‐US imaging of the prostate is validated. The YouTube link is here: https://youtu.be/U2Svj-4Ae_k